Automatic â€œDiverâ€ Observation and Pumping Simulation of Polder Drainage System, Case Study on Terboyo, Semarang, Indonesia - Sudirwan, Iwan; Wahyudi, S. Imam; Lekkerkerk, Jonathan (International Journal of Sustainable Construction Engineering and Technology, 2020)
One of the area inundated by flood and sea level rise (rob) in northern of Semarang city is Unissula campus and Terboyo terminal. The inundation in this area is caused by the high of sea levels (rob), so this area is often inundated by flood and rob during rainfall and high tide. The pumping simulation should be carry out in that area. By calculating and evaluating the river reservoir capacity towards the inflow such as hydrograph of design discharge of 10 years return period. Based on the observation results of water level elevation by the automatical â€œdiverâ€, it discovered that the sea level elevation is higher than water level elevation in the land area. To keep the water elevation in Unissula-Terboyo area that is +1.00, so pumping should be working. The one of simulation results with 1.25 m3/s pump capacity is +1.12 m highest water level elevation and pump is active for 11 hours to reach + 0.95 m elevation. According to the in situ experiment, Polder system and its storage quite effective to maintain water elevation.